Comparison of acute physiological adaptations between three variants of a basic head-out water exercise - Georgina Costa; Sandra Afonso; José Augusto Bragada; Victor Machado Reis; Tiago M. Barbosa (Universidade Federal de Santa Catarina, 2008)
http://dx.doi.org/10.5007/1980-0037.2008v10n4p323 The aim of this investigation was to compare the acute physiological adaptations to several variants of the same basic head-out aquatic exercise (only with legs actions, with simultaneous legs and arms actions, with simultaneous legs and arms actions using buoyancy dumb-bells). 16 young females, clinically healthy and with a regular level of physical activity were studied. Each subjected performed a basic head-out aquatic exercise named "rocking horse". Before and after each 6 minutes exercise, rate of perceived exertion (RPE) and blood lactate (La-]) were evaluated. Before, during and after each exercise, the maximal heart rate achieved (FCmax) was measured and the percentage of maximal theoretical heart rate estimated (%FCmax). The subjects perceived an increasing exertion from the exercise only with legs actions to the exercise with simultaneous legs and arms actions, to the exercise with simultaneous legs and arms actions including dumb-bells. The cardiac workout (FCmax and %FCmax) was significantly lower performing the exercise only with the legs than in the other two exercise conditions. The increasing number of limb's actions and the adoption of dumb-bells promoted an increase of the blood lactate. In conclusion, the increasing number of simultaneous limb's actions and the inclusion of materials, just like buoyancy dumb-bells, increased the acute physiological response in head-out aquatic exercises.